2021
DOI: 10.1371/journal.ppat.1009545
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of the zinc finger antiviral protein

Abstract: The human zinc finger antiviral protein (ZAP) recognizes RNA by binding to CpG dinucleotides. Mammalian transcriptomes are CpG-poor, and ZAP may have evolved to exploit this feature to specifically target non-self viral RNA. Phylogenetic analyses reveal that ZAP and its paralogue PARP12 share an ancestral gene that arose prior to extensive eukaryote divergence, and the ZAP lineage diverged from the PARP12 lineage in tetrapods. Notably, the CpG content of modern eukaryote genomes varies widely, and ZAP-like gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 38 publications
3
67
2
Order By: Relevance
“…However, many vertebrate viruses, including RNA viruses that do not have a DNA intermediate, show CpG suppression in their genome and introducing CpG dinucleotides into the genomes of diverse viruses inhibits their replication [18,[22][23][24][25][26][27][28][29][30]. While CpG dinucleotides in viral genomes may have multiple deleterious effects on replication [31][32][33], since ZAP has been shown to specifically bind CpG dinucleotides in viral RNA and restrict replication, it has been proposed that ZAP at least partially drives the CpG suppression observed in many vertebrate RNA viruses [18,34,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many vertebrate viruses, including RNA viruses that do not have a DNA intermediate, show CpG suppression in their genome and introducing CpG dinucleotides into the genomes of diverse viruses inhibits their replication [18,[22][23][24][25][26][27][28][29][30]. While CpG dinucleotides in viral genomes may have multiple deleterious effects on replication [31][32][33], since ZAP has been shown to specifically bind CpG dinucleotides in viral RNA and restrict replication, it has been proposed that ZAP at least partially drives the CpG suppression observed in many vertebrate RNA viruses [18,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…ZAP restricts HIV-1 replication when CpGs are enriched in the 5’ region of HIV-1 env more efficiently than when CpGs are enriched in other regions of the viral genome and introducing CpGs into this region creates a highly ZAP-sensitive HIV-1 [ 18 , 33 , 35 ]. This model ZAP-sensitive virus has been used to characterize the role of CpG dinucleotides in ZAP-mediated restriction and study its cofactors such as TRIM25 and KHNYN [ 13 , 18 , 19 , 34 ]. While the RNA binding domain (RBD) of ZAP is crucial for its selective antiviral activity [ 7 , 17 , 19 , 20 ], much less is known about the functional relevance of the other domains and motifs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to ZAP's RBD, the CaaX motif appears to be extremely well conserved in mammals and even birds. A recent study suggested that avian ZAP RBD has lower CpG-specificity than mammalian proteins [29]. It is thus likely that the evolution of CaaX happened after the duplication of genes that gave rise to PARP12 and ZAP, but still preceded the RBD adaptations that enabled efficient CpG-specific viral inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…ZAP more efficiently targets CpGs in the 5' region of HIV-1 env than other regions of the viral genome and introducing CpGs into this region creates a highly ZAP-sensitive HIV-1 [18][14] [28]. This model ZAP-sensitive virus has been used to discover and characterize ZAP cofactors such as TRIM25 and KHNYN [14] [29].…”
mentioning
confidence: 99%
“…[265] ZAP specifically binds to cytosineguanine (CpG) dinucleotides that are rare in mammals but common in many viruses, possibly as an evolutionary adaptation. [266] The new RNA-ZAP complex conformation enables ribonucleases to degrade the RNA molecule, thus preventing virus replication. [265] During its function, recent studies suggest that ZAP also activate and facilitate cytokine production by T-cells.…”
Section: Human Zinc Finger Antiviral Proteinmentioning
confidence: 99%